Type 1 Diabetes Mellitus Patients' Self-perception of Periodontal Diseases - Zainal Abidin, Zaridah; Noor, Erni; Mohd Nor, Noor Shafina; Mohamed Nazari, Nor Shafina; Anuar Zaini, Azriyanti; Azizi, Nurul Zeety; Soelar, Shahrul Aiman; Shahrizad, Marshah Mohamad; Abdul Halim, Rohaida (European Journal of Dentistry, 2023)
Objectives The study aimed to evaluate type 1 diabetes mellitus (T1DM) patients' self-perceived periodontal health status and to identify the association between periodontal disease (PD) and DM.Materials and Methods This cross-sectional study included 113 T1DM children between 3 and 18 years old from the Universiti Teknologi MARA and the University of Malaya. Periodontal health parameters, including plaque index, gingival index, probing pocket depth, simplified basic periodontal examination, and clinical attachment loss, were recorded. Self-perceived periodontal health status was assessed with questionnaires.Statistical Analysis Statistical analysis was performed to evaluate the sensitivity of the questionnaire and the relationship between T1DM and periodontal parameters.Results The median age was 11.4 years. Half of them (50.4%) were females. A total of 83.5% rated their oral condition as good, whereas 27.5% reported a history of gingival bleeding. Clinical examination revealed that 48.7% had healthy gingiva, whereas 47.8% had gingivitis. The question “Do you have bleeding when brushing, flossing, or eating food?” showed good accuracy in the evaluation of PD (p < 0.001).Conclusion The questionnaire has a high potential to be used by medical professionals in identifying T1DM patients at risk of PD to guide nondental health care providers in making appropriate referrals to dental services.
Keywords: periodontal disease; type 1 diabetes mellitus; diabetes mellitus; oral health; self-perception